Effect of Supplementation of Moringa oleifera (LAM) Leaf Meal in Layer Chicken Feed - Gakuya , D.W.; Mbugua, P.N.; Mwaniki, S.M.; Kiama, S.G.; Muchemi, G.M.; Njuguna, A. (International Journal of Poultry Science, 2014)
The purpose of this study was to investigate the effect of supplementing Moringa oleifera leaf meal (MOLM) at different levels in layers feed. Layers mash was formulated using raw materials obtained from local feed manufacturers and MOLM was included in the various diets at levels of 0% (T1), 1.25% (T2), 2.5.% (T3), 5% (T4), 7.5% (T5), 10% (T6). Diet 1 (T1) was added Canthacol® at a rate of 1 g/kg of feed while diet 7 (T7) was a commercially prepared feed. Twenty eight thirty week-old ISA Brown layer birds were selected from a flock and randomly allocated to seven treatment groups with 2 replicates of two birds each and the diet feeds introduced. Feed intake, weight gain, egg production, egg yolk color, egg weights, egg yolk color acceptability were determined. Eggs from randomly selected outlets of 4 leading supermarkets had their egg yolk colour score determined. The increase in MOLM levels had no effect on feed intake, weight gain, acceptability of boiled eggs by consumers and egg weights (p<0.05). The average egg yolk color score and the total eggs laid in the various treatments were significantly different (p<0.05) depending on the levels of MOLM in the diets. However, there was no significant difference in egg yolk colour score between the eggs from MOLM diets and those from supermarkets. There is need to investigate further the factors responsible for the yellow-orange colour of the eggs and the possibility of utilization of MOLM in commercial layers feed production.